(untitled) (Journal of Oriental Studies, 2019)
In this article the special features of Chinese language are described. The analyses of the basic lexi cal, grammatical, syntactic problems of translation from Chinese into Kazakh language are carried out. Brief determinations to them and examples were given. Attention to several problems was inverted, in order to carry out a translation from Chinese into Kazakh language without the barrier. The first – cor rect knowledge of Chinese hieroglyphs. The second – adequate translation of multimarking words. The third – the concrete translation of common words and scientific terms. The fourth – this is the ability un derstand clearly the difference of hieroglyphs, which forms are same, but pronunciations and meanings are different. The fifth – the basic grammatical special features of modern Chinese language. Taking into account these special features, it was shown the best methods of translation from Chinese into Kazakh language. Key words: Chinese language, hieroglyph, translation, morphology, auxiliary words, quantitative words, verb, noun, pronoun, subject, predicate, object.